Analysis of Sate Bulayak Micro, Small, and Medium Enterprises (MSMEs) in Advancing the Traditional Economic and Tourism Sector in Sesaot Village - Baiq Deswita Karina; Nayla Elsi Abidin; Winda Miranti; Resti Julia; Gheyzna Scharsza; Raquan Mulachela; Aldian Azahari; Yulanda Trisula Sidarta Yohanes (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This study aims to identify the challenges and development potential of sate bulayak as a local culinary icon supporting the Aik Nyet ecotourism area in Sesaot Village, Narmada District, West Lombok Regency. Using a qualitative approach and participatory method, this research explores in-depth insights through semi-structured interviews, participatory observation, and document analysis. Data were collected from sate bulayak vendors with over 20 years of experience and stakeholders involved in managing the tourism area. The findings reveal that while sate bulayak holds significant potential to attract tourists, several challenges persist, including inadequate waste management, poor road accessibility, and the habit of visitors bringing outside food, which affects local vendors' revenue. Proposed solutions include infrastructure improvements, enhanced waste management, policies providing incentives for local vendors, and intensified promotional efforts to expand the area's tourism appeal. This study highlights the importance of collaboration among the community, vendors, and the government in sustainably developing the economic and tourism potential of local culinary offerings in Sesaot Village.